2016
DOI: 10.1097/iae.0000000000000712
|View full text |Cite
|
Sign up to set email alerts
|

Thinking Lean

Abstract: Decentralized OCT represents the application of lean process concepts to improve vitreoretinal clinic efficiency. Decentralized OCT reduced both the total wait time and total time in clinic for return patients in a vitreoretinal clinic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…Such brief measurements could further improve clinical efficiency, which was previously slow, regarding new concepts for the use of decentralized OCT imaging. 25 …”
Section: Discussionmentioning
confidence: 99%
“…Such brief measurements could further improve clinical efficiency, which was previously slow, regarding new concepts for the use of decentralized OCT imaging. 25 …”
Section: Discussionmentioning
confidence: 99%
“…Historically, eye examinations in hospital eye clinics have been fragmented, inefficient, and costly. 4 6 , 8 The binocular OCT prototype combines many routine tests into one single instrument, with the aim of improving the speed and efficiency of patient flow, in addition to providing reproducible and quantitative data for several aspects of the eye examination. Designed as an automated, patient-operated device, usability testing is indispensable to predict the likelihood of future successful implementation in eye clinics.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, the median time taken to complete the examination was 702 seconds (11.7 minutes) for participants with chronic eye disease and 638 seconds (10.6 minutes) for healthy controls. By comparison, Callaway et al 8 reported a mean clinic time of 28.8 minutes for patients to undergo technician work-up (including history-taking and visual acuity measurement), and acquisition of retinal OCT in the photography suite. In many real-world settings, mean diagnostic testing time is likely to greatly exceed this, particularly in public healthcare settings, which are often overburdened and under resourced.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This approach has also been used in outpatient retina clinics, shortening wait times by changing photography workflow, adjusting staffing, and optimizing scheduling. 4,15 In this study, we use a comprehensive quality improvement approach, based in part on the aforementioned Lean Six Sigma methodologies, to determine strategies for reducing total visit duration in an academic ophthalmology department. Total visit duration is defined as the time from the patient's scheduled appointment to when they check out of the clinic.…”
mentioning
confidence: 99%